The strategic role of GCC Islamic banks in Malaysia: a knowledge transfer perspective - Elmabrok, Ali Abusalah; Ng, Kim Soon; Baig, Javaria (American Scientific Publishers, 2018)
The recent trend in the field of strategic management has been to emphasize the role of knowledge management as a basis of the competitive advantage of organizations. Historically, the searches for MNCs performance have been oriented around that knowledge is power. In organizations, this expression has become even more relevant than other social settings. Knowledge is a major factor that differentiates successful organizations from the unsuccessful ones. This study aims to investigate the strategic role in knowledge transfer, as well as to review the effect of strategic role as the constituent factor of knowledge transfer which contributes to the success of Islamic banking and financial knowledge performance in GCC Islamic banks subsidiaries in Malaysia. The data were collected through sending out questionnaires to 5 leaders of Upper Managers in GCC Islamic banks in Malaysia, administered 2-items of strategic roles namely: Contributor and Implementer. The respondents’ answers were subjected to SPSS. After that, semi-structured interviews were conducted with respondents. The results indicated that there is positive and significant influence of strategic leadership on knowledge transfer process. GCC Islamic banks subsidiaries in Malaysia are standing at the great extent level of strategic role from knowledge transfer perspective. In addition, the two factors named contributor and implementer lead to achieve the strategic role between headquarter and its subsidiary. The conclusion of this research paper recommended the advanced empirical research studies in future to develop a conceptual unifying model of Islamic banking and financial knowledge transfer within Islamic banks.